Gratitude Intervention Evokes Indebtedness: Moderated by Perceived Social Distance - He, Wuming; Qiu, Junjie; Chen, Yingying; Zhong, Yufang (Frontiers in Psychology, 2022)
Previous research suggests that gratitude intervention evokes indebtedness among people from an interdependent society. The current study furtherly hypothesized that perceived social distance moderates the effect of gratitude intervention on felt indebtedness. Two hundred and seventy-five adolescents were randomly assigned to three gratitude intervention conditions writing gratitude to significant others, the health of one’s own, or nothing. After completing the writing task, they rated their experienced emotions on ten dimensions, including gratitude and indebtedness. They also reported perceived social distance from surrounding people and other demographical information. Results indicated that participants in the condition of writing about gratitude to significant others felt indebted regardless of perceived social distance, while those in the condition of writing about gratitude to his/her own health and those in the control condition experienced lesser indebtedness as the perceived social distance with others becomes closer. Gratitude increases as perceived social connectedness increases across all conditions. Theoretical and practical implications were discussed.